Corrosion effects on pullout behavior of hooked steel fibers in self-compacting concrete - Frazão, Cristina Maria Vieira (2016)
Fiber reinforced concrete structures are subjected to chloride and carbonation penetration that could initiate corrosion of steel fibers, with eventual pernicious consequences in terms of structural and durability performance. Cracks in concrete are known to hasten initiation of steel corrosion in reinforced concrete structures. The investigation of the impact of cracks on the corrosion initiation and the associated interfacial damage between concrete and steel fibers is important for understanding the mechanical behavior of steel fiber reinforced concrete. In the present work, with the aim of studying the corrosion action on the mechanical behavior of cracked Steel Fiber Reinforced Self-Compacting Concrete (SFRSCC), an experimental program was performed to characterize the corrosion of hooked-end steel fibers and to assess the fiber pullout behavior in cracked concrete, previously subject to the action of corrosion by exposure to aggressive chloride environment.